AKTIVITAS ANTIDIABETES EKSTRAK ETANOL DAUN DAN BATANG SIDAGURI (Sida rhombifolia) TERHADAP MODEL HEWAN DIABETES TIPE 2 - Aulia Nurfazri Istiqomah; Widhya Aligita; Hendra Mahakam Putra; Denny Galang; Hapipah Nurjamilah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2021)
Diabetes is a disease characterized by increased levels of glucose in the blood that occur due to a lack of insulin production or the cessation of insulin production in the body. Sidaguri herb (Sida Rhombifolia) is known to have antidiabetic activity. This study was conducted to evaluate the antidiabetic activity of the ethanolic extract of the leaves and stems of sidaguri (Sida rhombifolia) in animal of type 2 diabetes model and to find out which part is the most effective as antidiabetic. This research method is an in vivo experimental study. Mice were divided into 9 groups, that is negative control group, positive control group, Glibenclamide 0.65 mg/KgBW, sidaguri leaf extract at a dose of 3.5; 7; and 14 mg/KgBW, as well as sidaguri stem extract at a dose of 3.5; 7; and 14 mg/KgBW. The test was carried out curatively, the test animals except negative controls were given induction of alloxan monohydrate 80 mg/KgBW via the intravenous route, then after 3 days post-induction, fasting blood glucose levels were checked. The treatment was continued by giving therapy for 14 days via the oral route. The test parameters in this study were the measurement of blood glucose levels on days 0, 7, and 14, and pancreatic histopathology was also performed. The test results show that was found that the extract that gave the best antidiabetic effect was the ethanolic extract of sidaguri leaves at a dose of 14 mg/KgBW but had not been able to fully improve the condition of the pancreatic cells